Effectiveness of Indian Advertisements in Breaking Stereotypes : A Comparative Analysis Using the Hierarchy of Effects Model - Nandi, Shampa; Bhat, Sudhindra; Wolfs, Bert (Indian Journal of Marketing, 2019)
A recent trend in Indian advertisements is that marketers deliberately send messages through advertisements to question the century old Indian conventional practices and challenge the stereotypes. The present study attempted to do a comparative analysis between the effectiveness of advertisements with unconventional messages with that of normal advertisements. In this study, the hierarchy of effects model (Lavidge & Steiner, 1961) was used for measuring the effectiveness of the advertisements which added some unconventional flavours in the ads and delivered messages to break norms. An empirical study based on one-group pre-test post-test experiment was done in June - July 2018, where several unconventional advertisements were shown along with other conventional advertisements among a group of 115 viewers. A structured questionnaire having established scales was utilized to measure the effectiveness of unconventional advertisements in terms of three dimensions of hierarchy of effects model - cognitive component (awareness, knowledge) ; affective component (liking, preference) ; and conative component (conviction, purchase). Data were analyzed with the help of Excel and SPSS by using statistical techniques like mean, standard deviation, ranking, regression analysis, Z - test, and ANOVA. The results confirmed that there were significant differences observed in case of all three dimensions along with ad appeal, ad recall, ad references, message impact between the advertisements with unconventional messages and normal advertisements. In summary, the influence of unconventional messages added in the advertisements improved the perception of the brands, enhanced consumers' attitudes towards social issues, and particularly increased the effectiveness of the advertisements, and their scores were higher than that of normal advertisements.